2020
DOI: 10.1371/journal.pone.0243157
|View full text |Cite
|
Sign up to set email alerts
|

Equation for analyzing the peak power in aquatic environment: An alternative for olympic rowing athletes

Abstract: Purpose To develop an equation to provide the peak power (PP) through a specific stimulus performed in an aquatic environment, as well as to correlate morphological, anthropometric and strength variables with rowing performance. Methods The sample consisted of 16 elite young rowing athletes of both sexes (15.7 ± 1.21 years). The strength of upper limbs and lower limbs was verified. To analyze the PP, a 100-m Sprint test was performed on an indoor rowing type ergometer, and after a 72-hour wash-out, the test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Olympic rowing is a typical strength/power endurance sport in which physical fitness, strength, rowing techniques, and tactics influence rower success. The anthropometric length or breadth of the human body is almost entirely genetically decided and can hardly be altered within the range of training periodization ( Almeida-Neto et al, 2020 ). Numerous studies found that 2,000-m rowing ergometer performance was predicted by body mass, VO 2 max ( Almeida-Neto et al, 2020 ), age, height, weight, and body fat percentage ( Majumdar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olympic rowing is a typical strength/power endurance sport in which physical fitness, strength, rowing techniques, and tactics influence rower success. The anthropometric length or breadth of the human body is almost entirely genetically decided and can hardly be altered within the range of training periodization ( Almeida-Neto et al, 2020 ). Numerous studies found that 2,000-m rowing ergometer performance was predicted by body mass, VO 2 max ( Almeida-Neto et al, 2020 ), age, height, weight, and body fat percentage ( Majumdar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously verified by Durkalec-Michalski et al (2019) that lean mass is closely related to the level of aerobic and anaerobic capacity of rowers. Likewise, it was pointed out that young elite athletes of both sexes ( Almeida-Neto et al, 2020b ) and non-elite males ( Almeida-Neto et al, 2020c ) with biological maturation in advanced stages point to greater lean body mass levels compared to their delayed maturation peers. Consequently, pointing to higher androgenic hormone levels and better efficiency of glycolytic metabolism, thus generating higher levels of muscle power ( Rowland, 2008 ; Almeida-Neto et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine a priori the minimum sample size to develop the mathematical model, we used the effect size of 0.915, referring to the linear regression result (mathematical model for peak power X peak power in indoor rowing) found by Almeida-Neto et al [ 22 ]. We used the G*Power ® software (Version 3.0; Berlin, Germany) in the configuration “T family statistics for regressions” and an α = 0.05 and a β = 0.80 considering a single variable to perform the prediction.…”
Section: Methodsmentioning
confidence: 99%